Techonological progress and Chinese agricultural growth in the 1990s. - Wang, Xiaobing. (2008)
There was a sharp recovery from stagnation and substantial increase in the grain production in China when more market-oriented reforms took effect in the 1990s. The decision regarding the agricultural production operation and adoption of new technology was fully given to the rural households by then. This basic observation shows that individual farmer and family calculations in China are responsive to innovation and policy change.